Dukungan Sosial Guru dengan Regulasi Diri dalam Belajar pada Siswa SMK - Yanti Saepito Yanti; Marselino K. P. Abdi Keraf; Diana Aipipidely (Universitas Nusa Cendana, 2020)
This study is a kind of correlational study that uses quantitative method. This study aims to know “the correlation of teacher’s social support towards self-regulated learning on students of SMK Negeri 1 Amabi Oefeto Timur “. The sample taken were 10th, 11th, and 12th grade students of SMK Negeri 1 Amabi Oefeto Timur consist of 64 students. The hypothesis testing used correlational testing of pearson product moment in recognizing both variables. The result showed that the value of correlational coefficient is 0,648 with has 0,000 significance value (p). Means that it is H1 (received), in this case there is a positive and significant correlation between teacher’s social support and self-regulated learning on students of SMK Negeri 1 Amabi Oefeto Timur. Keywords : Self-regulated learning, Teacher’s social support Bibliography 36 (2008-2019)